Greengram Crop Husbandry - International Crops Research Institute for the Semi-Arid Tropics (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
This brochure is a guide to cultivation of green gram. It provides the ideal climatic conditions for cultivation of the crop, covering aspects such as land preparation, seed rate, sowing, weed control, optimal fertilizer application and harvesting. It provides insights into managing common insect pests and diseases. Emphasizing integrated pest management as an effective environment sensitive approach to pest management, the brochure provides guidance on application of pesticides. Additionally, it offers valuable insights into post-harvest handling methods aimed at minimizing crop losses and ensuring the production of high-quality grain suitable for both household consumption and market demand.